Relationship between vaginal microecology and human papillomavirus infection as well as cervical intraepithelial neoplasia in 2,147 women from Wenzhou, the southeast of China - Zang, Lejing; Feng, Renqian; Huang, Yitong; Huang, Jiahe; Hu, Yan (Frontiers in Oncology, 2024)
The female reproductive tract is a significant microecological region, and its microenvironment can directly affect women's cervical health. This research aimed to investigate the effect of vaginal microecology on human papillomavirus (HPV) infection and cervical intraepithelial neoplasia(CIN).Methods ： A retrospective cohort study enrolling 2,147 women who underwent a colposcopic examination between August 2021 and August 2022 was conducted. The relationship between vaginal microecology and HPV infection as well as cervical lesions were assessed using the chi-square test, univariate and multivariate logistic regression analyses, and Cochran-Armitage trend test.Results：HPV infection was linked to the imbalance of vaginal microecology [odds ratio (OR)=3.00, 95% confidence interval (CI)=1.66-5.43; P<0.001]. Clue cell (OR=1.59, 95% CI=0.99-2.54; P=0.054) and sialidase (OR=1.54, 95% CI=1.01-2.35; P<0.046) were considered as significant risk factors for HPV infection. Further analysis showed that vaginal microecological disorder was more likely to be detected in patients infected with HPV 16/18 subtypes (OR=9.86, 95% CI=2.37-41.80; P=0.002). Although there was no significant correlation between the incidence of vaginal microecological disorder and the severity of cervical lesions (P > 0.05), the proportions of abnormal PH value (OR=2.6, 95% CI=1.63-10.42; P=0.001) and abnormal vaginal cleanliness (OR=2.6, 95% CI=1.36-4.0; P= 0.004) increased as the histological stage progressed.Conclusion：Vaginal microecology associates with HPV infection and the progression of cervical lesions. Detection of vaginal secretion may contribute to the development of targets for microenvironmental modulation with probiotics and the reduction of the incidence of cervical cancer.